Assessment of the Relationship between Craniofacial Measurements and Maxillary Central Incisor Width using Cone Beam Computed Tomography - Bandar Awadh Alresheedi (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aimed to explore the relationships between bizygomatic width, inter-orbital distance, and the central incisor width (CIW). Materials and Methods: A total of 80 cone beam computed tomography (CBCT) scans were analyzed. The measurements taken included bizygomatic width and inter-orbital distance. A bivariate correlation was performed to evaluate the relationships between CIW and craniofacial measurements. Independent samples t-tests were used to compare these measurements between genders. Results: Mean values for CIW and bizygomatic width were significantly higher in males than females (P < 0.05). The bivariate analysis revealed significant, positive, moderate correlations between CIW and bizygomatic width (r = 0.401, P < 0.01), but not inter-orbital distance (P > 0.05). Conclusion: This study found that while bizygomatic width is moderately correlated with CIW, inter-orbital distance is not. Additionally, significant gender differences exist regarding bizygomatic width and CIW, with males exhibiting larger dimensions.